2021
DOI: 10.1186/s40816-021-00314-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of bio-synthesized iodine-doped silver nanoparticle wound ointment in experimental rats

Abstract: Background In the wake of antibiotic resistance, treatment of intractable wound have been very challenging and any alternative treatment which may lead to less use of antibiotics deserves further exploitation. Nanoparticle conjugates has potentially not only reduce antibiotic use but it has been considered safe and effectively disinfect wounds already colonized with resistant bacteria as well as promoting granulation tissue formation. In this study, Iodine-doped silver nanoparticle Ointment (Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…4b-e). This is in contrast to the account by Shittu et al [49], who reported the unscathed nature of the hepatocytes after wound healing activity of silver nanoparticles. The PEG treated water groups revealed thrombosed and recanalized blood vessels and focal areas of necrosis (Fig.…”
Section: Histopathological Studiescontrasting
confidence: 99%
See 1 more Smart Citation
“…4b-e). This is in contrast to the account by Shittu et al [49], who reported the unscathed nature of the hepatocytes after wound healing activity of silver nanoparticles. The PEG treated water groups revealed thrombosed and recanalized blood vessels and focal areas of necrosis (Fig.…”
Section: Histopathological Studiescontrasting
confidence: 99%
“…Hb and PCV are involved in the transport of nutrients and oxygen to tissues to enhance energy release for the body [48]. While, granulocytes are the innate immune system cells that have the ability to generate antibodies, fight microbial infections, respiratory complications and allergies [49,50]. MCV, MCH, MCHC are valuable parameters used in diagnosing different types off anaemia and monitoring toxicity that may alter blood or health status of an animal [46].…”
Section: Haematological Studiesmentioning
confidence: 99%
“…Hb and PCV are involved in the transport of nutrients and oxygen to tissues to enhance the release of energy for the body (Isaac et al, 2013). Granulocytes are cells in the innate immune system that helps to ght microbial infections, respiratory complications, allergies and have the ability to generate antibodies by phagocytosis (Shittu et al, 2021;Okunlola et al, 2015).…”
Section: Studiesmentioning
confidence: 99%
“…It should also be noted that silver is effective against multidrug-resistant strains [ 15 , 16 , 17 ]. High antibacterial activity has led to the wide use of silver nanoparticles in medicine for the treatment of textiles [ 18 ], the creation of dressings [ 19 ], antibacterial ointments [ 20 ], etc. However, unanchored silver nanoparticles can easily be removed from the carrier material during operation.…”
Section: Introductionmentioning
confidence: 99%